T2 prolongation in the cerebellar vermis on prenatal MRI of fetuses with Chiari 2 malformations. Issue 5 (May 2019) - Warner, H.M.; Batty, R.; Warner, F.M.; Fanou, E.M.; Griffiths, P.D.
Abstract : AIM: To describe a new finding in fetuses with Chiari 2 malformations recognised at in utero (iu) magnetic resonance imaging (MRI), specifically T2 prolongation (high signal) in the cerebellar vermis. MATERIALS AND METHODS: This was a prospective observational study of iuMRI studies performed at two time points on 20 fetuses with Chiari 2 malformations and 10 control fetuses at the same time points. High T2 signal in the cerebellar vermis was noted and correlated with posterior fossa dimensions was assessed. RESULTS: High T2 signal in the cerebellar vermis was found in over half of the fetuses with a Chiari 2 malformation, but was not correlated with the degree of reduction in size of the bony posterior fossa. CONCLUSION: The present findings suggest that abnormal high T2 signal in the cerebellum is common in fetuses with Chiari 2 malformations and although the cause of the signal change is not known at present it may represent vasogenic oedema as a result of restricted venous drainage. Highlights: T2 prolongation was noted within the cerebellar vermis of foetuses with Chiari 2 malformation. The finding of T2 prolongation was independent of posterior fossa size in affected cases. No associated restricted diffusion was identified.